Strategy Selection in the Implementation of PT Kereta Commuter Indonesia's Security Management System in The Greater Jakarta Area - Mohammad Ridwan; Zainur Hidayah; Amir Tengku Ramly (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The purpose of this study is to describe a general description of the conditions of Security Management System (SMS) implementation in the PT KCI Greater Jakarta area, examine indicators that can affect the implementation of SMS at PT KCI Greater Jakarta area, and formulate a priority scale strategy for SMS at PT KCI Greater Jakarta area during the COVID-19 pandemic. The researcher uses Analytical Hierarchy Process (AHP) method by including six indicators of field certification, employee skills training, reporting & administration, archive documentation, and performance evaluation as the selection of indicators that affect implementation, and three alternative selection strategies, namely training competencies, documentation & records, and controls & processes. The results showed that the most influential indicators were the Documentation Archive 0.331, Reporting & Administration 0.223, and Operational Control 0.203, while the appropriate alternative strategies to determine steps in implementing SMS during the covid-19 pandemic were Documentation & Records 0.594 and control and process 0.262. The results imply that to achieve the successful implementation of the SMS program at PT KCI, a document filing system and good operational control are needed in each security unit.